Education, Inspection and State Formation: A Preliminary Statement - Corrigan, Philip; Curtis, Bruce (Historical Papers / Communications historiques, 1985)
AbstractThis paper attempts to draw the attention of sociologists and historians of education to the matter of the form of public schooling. A review of competing models of educational development current in the literature shows that neither pays attention to public schooling as a form of state provided and regulated schooling. Current models thus neglect the implication of schooling in the organization of patterns of government. The article argues that public schooling came to be normalized as what education really was (or should be). To pursue this argument it investigates the inspective function as one of the key processes whereby public schooling was administered into dominance. While the discussion centres on North American experience, English material is also discussed in an effort to locate the construction of the educational state in its broader context.